Coenopopulations of Myricaria bracteata Royal at the territory of the Republic of Kazakhstan and their ontogenetic structure - Lyakh Elena M.; Astashenkov Alexey Yu. (BIO Web of Conferences, 2019)
The article represents the analysis of 4 Myricaria bracteata populations in Kazakhstan. It was found that ontogenetic spectrum reflects the development degree of coenopopulations related to succession processes of riparian communities. Depending on the floodplain width, free space and phytocenotic pressure, the ontogenetic spectrum and stability of coenopopulation vary from left-sided incomplete to centered incomplete; from unstable invasive (in a narrow floodplain) through successive transitional and young normal to mature normal stable (in a wide floodplain) ones.